Public debt and macroeconomic stability among sub-Saharan African countries: a system GMM test approach - Jerry Ogutu Sumba; Rogers Ochenge; Paul Mugambi; Collins Muimi Musafiri (Cogent Economics & Finance, 2024)
This study examined the effect of public debt on macroeconomic stability among 45 sub-Saharan African (SSA) countries for the period 2005-2022 using the two-step system Generalized Method of Moments (GMM). The study disaggregated public debt into domestic and foreign borrowing and determined the effect of each on inflation and economic growth. In agreement with recent studies, we found compelling evidence of negative effect of both domestic and foreign borrowing on economic growth and a positive effect on inflation among SSA countries. The empirical results reveal that a unit increase in domestic borrowing reduces economic growth by 0.06 percent and raises inflation by about 0.14 percent, while the same increase in foreign borrowing reduces economic growth by 0.01 percent and increases inflation by 0.05 percent holding other factors constant. These results imply that increase in public debt causes macroeconomic instability, and that domestic borrowing has a relatively larger impact on macroeconomic variables compared to foreign borrowing. The policy implication of the current study is that SSA countries should avoid excessive borrowing by operating a fiscal deficit within individual country threshold limits to contain growth in public debt. The SSA countries should also ensure borrowed funds are channeled into projects that bring revenue and other investment opportunities to amortize the debt stock. Accumulation of public debt tend to have a negative impact of the countries macroeconomic stability depending on how it is financed. This is common especially in developing countries where different debt instruments among them domestic and foreign borrowing are used as mean to mobilize financial resources for covering budget deficit as well as investment in development projects. This study determines the effect of public debt (domestic and foreign) on main macroeconomic variables (inflation and economic growth) to determine the effect of each tool on the selected variables in sub-Saharan African countries. The results of this study will help the policy makers in choosing appropriate debt instrument to minimize negative effect on macroeconomic stability.
Keywords: 330; Public debt; economicgrowth; inflation rate; macroeconomic; domestic borrowing; foreign borrowing; system GMM